Elasticity and Rupture of Finger Jointed Mango Wood Joined with Two Adhesives - Kishan Kumar, V. S.; Gupta, Sachin; Kothiyal, Vimal (Indian Forester, 2011)
Effectiveness of finger jointing was assessed in utilising lower quality mango wood which is extensively used by handicrafts industries in India. The study was based on the estimation of Modulus of elasticity (MOE) and Modulus of Rupture (MOR) under static bending of finger jointed sections and comparing them with the values measured for clear wood sections from the same lot. It was found that the MOE of the sections joined by Urea Formaldehyde adhesive showed significantly better values than that of even unjointed sections. The MOR values of such jointed sections were similar to those of unjointed clear wood sections. Sections jointed through Polyvinyl Acetate adhesive exhibited lower MOR and MOE values.